The investigation of the relation between INR levels and risk of complication in patients with a history of Warfarin use [Varfarin kullanım öyküsü olan hastalarda, inr deǧerleriyle komplikasyon gelişim risk i̇lişkisinin ortaya konması] - (:unkn) unknown (Marmara University, 2012)
Objective: Warfarin is the most commonly used oral anticoagulant agent. In overdose situations, serious complications may occur. The aim of the study was to determine the correlation between the international normalized ratio (INR) levels and complications due to warfarin. Patients and Methods: The study was performed prospectively at the Department of Emergency Medicine, Marmara University Hospital between July 2006 and July 2007. Patients whose complaints were due to warfarin overdose were included in the study. The presentations and outcomes of these patients were analyzed. SPSS 15.0 was used for the analysis. The Chi-square test was used for the statistical analysis. The statistical difference p<0.05 is considered as significant. Results: During the study period, 105 patients with high INR levels were evaluated in the emergency department. 45.7% of these patients presented to the Emergency Service in less than 12 hours. INR levels were over 10.0 in 30.4%, and below 3.5 in 21.9% of the patients. 2 patients had to stay in the intensive care unit for following and treatment. There was no correlation between the INR levels and the bleeding risk (p>0.05). Conclusion: There is no significant correlation between the INR levels and the severity of the bleeding (p>0.05). © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Anticoagulant agents; Hemostasis; INR levels; Vitamin K; Warfarin